An experimental investigation on utilisation of floral foam as a coolant material to amp up the efficiency of solar PV panel. Issue 1 (31st December 2022) - Rajasekar, R.; Prasannaa, P.; Ramkumar, R.
Abstract : The photovoltaic cell performance can be affected by parameters such as operating temperature, irradiance and induced cell temperature. If the cell temperature increases, the PV module loses its conversion efficiency. So, it is necessary to maintain the temperature of a solar panel to extract the maximum efficiency in all the operating conditions. In our experimental work, a special cooling treatment was performed on the solar PV panel, using floral foam packs in the bottom surface and thin film of pot water flow over the top surface. As the pot water temperature always stays 5–8°C less than that of the ambient temperature, it was selected as a coolant medium, which absorbs the generated heat effectively. From the obtained results, it has been found that the efficiency of the PV panel with special cooling has improved the overall efficiency up to 60% more than that of the conventional PV panel.